Phylogenetic relationship of diadema: emphasis on the two distinct clades of d. setosum with the inclusion of long spine black sea urchin from Malaysian Borneo - Ruhana Hassan,; Nursyuhaida Md Shahid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Diadema urchins (family Diadematidae) are ecologically important bioindicators of coral reef ecosystems and seagrass beds. Diadema urchins which are widely distributed and broadcast spawners, have been frequently utilized as model invertebrate species for zoogeography research of the Indo-West Pacific region. So far, Malaysian Borneo, located at the geographic center of Maritime Southeast Asia, has been under-sampled. This study aims to fill this sampling gap and provide the first record of Diadema setosum from Malaysian Borneo using genetic diagnostics to conclusively establish the clade-level identity of the species. According to Cytochrome Oxidase I gene analysis, Diadema is monophyletic. Seven species of Diadema namely Diadema palmeri, Diadema clarki, Diadema mexicanum, Diadema antillarum, Diadema paucispinum, Diadema africanum, and Diadema savignyi, formed their subclades with strong bootstrap values, demonstrating interspecific variation. The findings of this study provide further evidence for the presence of two distinct monophyletic clades, with all D. setosum individuals forming a monophyletic clade that later split into two distinct subclades, dividing Red Sea population (D. setosum-b) and Indo-West Pacific populations (D. setosum-a), supported by a significant genetic divergence value ranging from 6.3% to 9.1%. This study also revealed notable levels of nucleotide and population subdivision between the D. setosum from the Indo-West Pacific and the Red Sea populations (Nst = 0.891; Fst = 0.886) with a low number of migrants per generation (Nm = 0.065). This may suggest geographic isolation due to ecological factors preventing each other from surviving in the territory of the other, or that the two clades of D. setosum were a separate species. Additional morphological and molecular analysis is required in the future to ascertain the level of divergence and further resolve the taxonomic confusion within the genus Diadema.